2010
DOI: 10.1038/ijo.2010.92
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of the Alström syndrome-associated gene Alms1 in 3T3-L1 preadipocytes impairs adipogenesis but has no effect on cell-autonomous insulin action

Abstract: Alström syndrome is a rare genetic syndrome associated with early-onset obesity, severe insulin resistance (IR) that is disproportionate to the degree of adiposity and premature diabetes. The ALMS1 gene, which is mutated in Alström syndrome, encodes a giant 460 kDa centrosome-and basal body-associated protein. Its function is unknown, although roles in primary cilia formation and function, intracellular organelle trafficking and, most recently, adipocyte differentiation have been mooted. We now test the hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 21 publications
4
31
2
Order By: Relevance
“…Two days after such treatment, proadipogenic peroxisome proliferator-activated receptor γ (PPARγ) was detected in BBS10 and BBS12-depleted preadipocytes, suggesting that a functional cilium/basal body can negatively regulate adipogenesis. These results are in contrast with studies showing a down-regulation of PPARγ suppression of Alms1 and IFT proteins in transformed 3T3-L1 mouse preadipocytes(Huang-Doran and Semple, 2010). However, given that human preadipocytes can proceed to terminal differentiation without post-confluence mitosis, differences in PPARγ responsiveness may be attributed to cell line-specific variables.…”
Section: Introductioncontrasting
confidence: 99%
“…Two days after such treatment, proadipogenic peroxisome proliferator-activated receptor γ (PPARγ) was detected in BBS10 and BBS12-depleted preadipocytes, suggesting that a functional cilium/basal body can negatively regulate adipogenesis. These results are in contrast with studies showing a down-regulation of PPARγ suppression of Alms1 and IFT proteins in transformed 3T3-L1 mouse preadipocytes(Huang-Doran and Semple, 2010). However, given that human preadipocytes can proceed to terminal differentiation without post-confluence mitosis, differences in PPARγ responsiveness may be attributed to cell line-specific variables.…”
Section: Introductioncontrasting
confidence: 99%
“…Marion et al showed that depletion of BBS12 decreases the ratio of cilium-positive cells and increases adipocyte differentiation [5]. On the other hand, affecting the primary cilium through a decrease in Alms [29], IFT88 or Kif-3A [30,31] expression inhibit adipocyte differentiation. These observations suggest that the primary cilium controls several steps of adipogenesis and cannot be considered only as a "switch" that triggers or inhibits adipocyte differentiation.…”
Section: What Could Be the Biological Function Of The Modulation Of Cmentioning
confidence: 96%
“…However, the effect on adipogenesis varies depending on the specific ciliary protein being affected. In contrast to BBS10 and BBS12, knockdown of ALMS1 (mutated in ALMS) in 3T3-L1 inhibited adipogenesis [135]. Depletion of the ciliary proteins Pkd1 and BBS12 also resulted in enhanced adipogenesis while inhibition of the IFT anterograde molecular motor Kif3a impaired adipocyte differentiation [136,137].…”
Section: Adipogenesis Defects In the Etiology Of The Bbs Related Obesitymentioning
confidence: 99%